Stabilitas Gas Karbondioksida pada Minuman Berkarbonasi selama Penyimpanan - Berliana Simanjuntak; Dede Robiatul Adawiyah; Eko Purnomo (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2016)
For carbonated soft drink, stability of carbondioxide (CO2) is one of the critical parameters as it is related to its sensory acceptance. The the presence of this CO2 creates a tingling sensation. The stability of CO2 is related to the permeability of its packaging, different ingredients used in the formulation and the chemicals reaction happened during storage. The purpose of this research is to analyse the changes in volume and solubility of CO2 stored at three different temperatures (6, 25, 55oC) in three different packaging (can, glass and bottle). Later on its half-life (t1⁄2) was calculated based on Arrhenius method. The result showed that CO2 volume lost in plastic was about 0.002% per day at 6oC, 0.003% per day 25oC and 0.007% per day at 55oC. Solubility of CO2 the decreased at 55oC. In plastic, it was 0.026% per day while glass and can stored at the same temperature was 0.019% per day. The half-life (t1⁄2) of this product packaged in can at 25oC) was 206 days (7.0 months), 200 days (6.7 months) packaged in glass and 104 days (3.5 months) packaged in plastic. The initial volume of CO2 of the products used in this research was varied.